Sir Cumference and the Viking's map : a math adventure - Neuschwander, Cindy; Geehan, Wayne (Watertown, MA : Charlesbridge, 2012)
"Xaxon Yellowbearyd was the fiercest Viking warrior of his time. Now a map to his hidden treasure lies in the hands of Radius and Per. Together the cousins must decode the strange numbered grid on the map--and figure out the secret of the Viking's X and Y axes. As bandits pursue them, Radius and Per track down clues and use coordinate geometry in their quest for "treasure of the greatest measure"."--Dust jacket flap.
Keywords: Coordinates -- Juvenile literature; Geometry, Analytic -- Juvenile literature; Coordinates; Geometry, Analytic